(3TQM GdcaGjIs - (3GdfLaj, GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg HfMh GdYjfjI Cj GdPj jbJVj Gdfgj Yf VOg dCf Gdfgj Yf GdVO Yjf GdCeQ GeG eagheG Ch eUOGbG bhdg ef LgI GdcdGes
(3BNQgG (B:s
(3BNQgG(B: (3bhdg dG jcGO jJYdb HWHjYI hGMOI eQJjf dCfg jdRe Cf jchf gfGc (B.. (3fMh TjA hGMO ef TNU hGMO ajdRe GLJeGY GdeKdjf aj TjA hGMO hgh HGWd(B. (3Je GdcdGe aj GdebUO GdChd, hSjLjA GdcdGe aj GdebUO GdKGfjs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg aj fgGjI GdLRA GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs